Evaluation of the Multiple Sclerosis Spasticity Scale 88: A Short Report. (January 2019) - Freeman, Jenny; Gorst, Terry; Ofori, Jodielin; Marsden, Jonathan
Background: The Multiple Sclerosis Spasticity Scale 88 (MSSS-88) is designed to capture the patient experience and impact of spasticity, but there is limited evaluation against clinician-rated measures of spasticity. Objective: To evaluate the convergent validity and responsiveness of the MSSS-88. Design: Longitudinal study. Setting: University Laboratory. Subjects: Thirty-four people with multiple sclerosis. Methods: People with multiple sclerosis (MS; n = 34) completed the self-reported 12-item Multiple Sclerosis Walking Scale, Multiple Sclerosis Spasticity Scale, Barthel Index alongside the clinician-rated Ashworth Scale, and a laboratory-based measure of ankle spasticity. Spasticity measure responsiveness was evaluated in 20 participants at two time points, an average of 8.75 ± 3.8 months apart. Results: In people with MS (mean age 55.1 ± 8.1 years; Expanded Disability Scale range 4.5-7.0), spasticity symptom specific subscales of the MSSS-88 (stiffness and spasms) showed strong and significant correlations with the clinician-rated Ashworth Scale ( r = 0.52-0.53; P < .01). Responsiveness of the MSSS-88 was comparable to a laboratory-based measure of ankle spasticity. Conclusions: Our findings lend additional support to the convergent validity of this measure.